Factitious Cushing's Syndrome: A Diagnosis to Consider When Evaluating Hypercortisolism - Pineyro, Maria M.; Redes, Lia; De Mattos, Sylvana; Sanchez, Luciana; Brignardello, Estefania; Bianchi, Virginia; Ems, Vanessa; Centurión, Dardo; Viola, Marcelo (Frontiers in Endocrinology, 2019)
FFactitious Cushing’s syndrome is exceptionally rare. The diagnosis is challenging due to the interference of exogenous corticosteroids with cortisol immunoassays. We present a case of a 26-year old female that presented with clinical and biochemical features of Cushing’s syndrome. She denied any exogenous corticosteroid use. She had a suppressed ACTH level with normal adrenal glands on CT scans. There was a paradoxical increase of cortisol with a 100% rise in 24-hour urinary free cortisol (UFC) during the Liddle’s test suggestive of primary pigmented nodular adrenocortical disease (PPNAD). However, basal UFC levels were within normal values, interpreted as an intermittent variation of cortisol secretion maybe due to cyclic Cushing’s. At this point a synthetic glucocorticoid serum screening was ordered, which was denied by the administrators because the test was not available in our hospital. A positron emission tomography (PET)-CT using F-Flurodeoxyglucose did not show any uptake in the adrenal glands. With the diagnosis of probable primary pigmented nodular adrenocortical disease (PPNAD) a unilateral right adrenelectomy was performed. Histopathological examination revealed normal adrenal gland. A synthetic glucocorticoid serum screen by liquid chromatography-tandem mass spectrometry (LC-MS/MS) sent to Mayo Clinic lab revealed high levels of serum prednisone and prednisolone. In conclusion, factitious Cushing’s syndrome is an important diagnosis to consider in patients being evaluated for hypercortisolism. Discordant hormonal test results as well as normal findings on adrenal glands on CT scan should raise suspicion of this entity, and prompt measurement of synthetic corticosteroids using LC-MS/MS.